Dynamics of changes in temperature of batch sterilizers with backpressure - Klymenko, Oleh; Petrenko, Valentin; Tregub, Victor (My University, 2017)
The article describes the construction of dynamic subsystem logical and dynamic model for batch sterilizer with counter pressure needed for the construction of programmer. To describe the dynamic of counter-pressure autoclave is used mathematical method that takes into account the sequence of the autoclave. Modeling scheme for areas of heating and shutter, and cooling area are programmed in MatLab with the heat balance equation. There are circuit modeling temperature changes in blanks in areas of heaing and shutter speed and cooling section.
Keywords: dynamic subsystem; sterilizer; autoclave; heat balance; динамічна підсистема; стерилізатор; автоклав; тепловий баланс; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка